If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9(x + 4) = 3(x + 24) Reorder the terms: 9(4 + x) = 3(x + 24) (4 * 9 + x * 9) = 3(x + 24) (36 + 9x) = 3(x + 24) Reorder the terms: 36 + 9x = 3(24 + x) 36 + 9x = (24 * 3 + x * 3) 36 + 9x = (72 + 3x) Solving 36 + 9x = 72 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 36 + 9x + -3x = 72 + 3x + -3x Combine like terms: 9x + -3x = 6x 36 + 6x = 72 + 3x + -3x Combine like terms: 3x + -3x = 0 36 + 6x = 72 + 0 36 + 6x = 72 Add '-36' to each side of the equation. 36 + -36 + 6x = 72 + -36 Combine like terms: 36 + -36 = 0 0 + 6x = 72 + -36 6x = 72 + -36 Combine like terms: 72 + -36 = 36 6x = 36 Divide each side by '6'. x = 6 Simplifying x = 6
| .5c=2.25 | | 7n-1=5n+n | | 17.50=5.8x+3 | | X^2-X=21 | | 5(x-4)=25-4x | | 15=-3(-1+-4) | | -8y=120 | | -3x-5(2x-5)=6(3x-10) | | 3x+2x=5x^2 | | 2x-4=80x-10 | | (1.06)x=2000 | | 81=(t-(-4))+11 | | 3y-2y=1-2x | | b-2+8b=26 | | 113+3x+46+90=720 | | 2x-8=8-2x | | 4=5(54) | | 4(-2x)+6=14 | | 1-8=-9z | | (x+36)+2x+(x+36)+180=540 | | 5533+522522= | | 7n+30=2n-25 | | 15(1t+6m)+9t=6 | | 7x-24+5x+18=180 | | x^2-3x=29 | | (3f)+2=11 | | -8st+5t+2u-1=8t+9u-9 | | 170=45t | | 10b-9-3b=2 | | 170-t=45 | | 45=170t | | 4x-6-5x-5=x-4 |